Short-scale variability of the SCLM beneath the extra-Andean back-arc (Paso de Indios, Argentina): Evidence from spinel-facies mantle xenoliths - Ponce, Alexis Daniel (2015)
Cenozoic basalts carrying ultramafic mantle xenoliths occur in the Matilde, León and Chenque hills in the Paso de Indios region, Argentina. The mantle xenoliths from the Chenque and León hills mainly present porphyroclastic textures, whereas the Matilde hill xenoliths have coarse-grained to porphyroclastic textures. The equilibrium temperatures are in the range of 780 to 940°C, indicating a provenance from shallow sectors of the lithospheric mantle column that were subjected to a relatively low heat ffiux at Cenozoic Era. According to the modal compositions of xenoliths, the mantle beneath Matilde and León hills was affected by greater than 22% partial melting, while less depleted peridotites occur in the Chenque suite (starting from 10% partial melting). Such an observation is confirmed by the partial melting estimates based on Cr# Sp , which vary from 8 to 14% for the selected Chenque samples and from 14 to 18% for the Matilde ones. The common melting trend is overlapped by small-scale cross cutting local trends that may have been generated by open-system processes, such as open-system partial melting and/or post partial-melting metasomatic migration of exotic Na-Cr-rich melts. The two main mineralogical reaction schemes are: i) the dissolution of pyroxenes and the segregation of new olivine in olivine-rich peridotites, and ii) the replacement of primary olivine by orthopyroxene±clinopyroxene in orthopyroxene-rich peridotites. These were produced by channelled and/or pervasive melt extraction/migration. Enhanced pyroxene dissolution is attributed to channelling of silica-undersaturated melts, whereas the replacement of primary olivine by orthopyroxene±clinopyroxene points to reaction with silica-saturated melts. Late disequilibrium reactions identified in the xenoliths comprise: the breakdown of orthopyroxene in contact with the host basalt, and (rarely) reaction coronae on orthopyroxene, clinopyroxene and spinel linked to glassy veins. Such features are apparently related to the injection of melt, likely during entrainment into the host basalts and ascent to the surface.